Analyzing the Relationship Between Preventative Healthcare Utilization and Higher Education Levels in Underserved Los Angeles Communities - Ahmad Elhaija; Harshita Ravi (International Journal of Medical Students)
BACKGROUND: Despite significant advancements in scientific research to reduce the risk of various illnesses and health conditions, the underutilization of preventive healthcare poses a significant barrier to enhancing public health outcomes.1 A 2020 study found that only 8% of Americans undergo routine preventive care screenings2; racial minorities such as Hispanic Americans are even less likely to receive preventive health services due to socioeconomic disparities.3 Individuals with higher educational attainment are more likely to receive routine health checkups4, and have higher vaccination rates.5 To illustrate these dynamics, this case focuses on Maywood and Bell, two adjacent cities with large patient populations from immigrant and refugee backgrounds. Educational attainment rates, which represent the percentage of residents with at least a bachelor’s degree level of education, are notably lower in Maywood and Bell (8.7% and 8.8%) compared to California as a whole (37.0%). The percentage of residents without health coverage in Maywood and Bell (18.0% and 13.9%, respectively) are higher than California’s average of 6.5%.6,7